The European Union's Competitive Position in Relation to the Asian Region - Talar, Sylwia (Pozycja konkurencyjna Unii Europejskiej w stosunku do Azji, 2010)
For the last several years differences in economic performance between the European Union and Asian countries have posed the question about changes on the world economic map in the future. One of the most interesting issues is competitive position of the EU in relation to Asian dynamic region. The aim of this paper is research on changes in the ability to: export, attract FDI and produce income in the EU and Asian region. The key conclusion is that the EU overall competitive position has not worsened for the last several years in relation to Asian region.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 80-89
Keywords: international competitiveness; European Union; Asia